Interaction Between Autophagy and Porphyromonas gingivalis-Induced Inflammation - Kang, Sen; Dai, Anna; Wang, Huiming; Ding, Pei-Hui (Frontiers in Cellular and Infection Microbiology, 2022)
Autophagy is an immune homeostasis process induced by multiple intracellular and extracellular signals. Inflammation is a protective response to harmful stimuli such as pathogen microbial infection and body tissue damage. Porphyromonas gingivalis infection elicits both autophagy and inflammation, and dysregulation of autophagy and inflammation promotes pathology. This review focuses on the interaction between autophagy and inflammation caused by Porphyromonas gingivalis infection, aiming to elaborate on the possible mechanism involved in the interaction.